Analisis Strategi Marketing Mix dalam Penguatan Daya Saing Produk UMKM Roti Kacang Mpok Atik di Kota Tebing Tinggi - Eggi Indriani Pratami; Nur Safitri; Ricki Steven Manalu (Economic Development Progress, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy. Roti Kacang Mpok Atik is a culinary MSME specializing in traditional peanut bread from Tebing Tinggi. Established more than eight years ago, this business continues to grow by maintaining its authentic taste and consistent product quality, making it one of the most popular local food products among consumers. This study aims to analyze the implementation of the marketing mix strategy in strengthening the product competitiveness of the Roti Kacang Mpok Atik MSME in Tebing Tinggi City. The research applies a descriptive qualitative method with data collected through interviews, observations, and documentation. The analysis focuses on four key elements of the marketing mix (product, price, place, and promotion) as essential factors for improving business competitiveness. The results indicate that the marketing mix implementation positively impacts the competitiveness of Roti Kacang Mpok Atik. Product quality and pricing strategies serve as the main strengths in building customer loyalty, while distribution and promotion aspects still require improvement through packaging innovation and digital marketing optimization. Overall, the consistent and adaptive integration of the four marketing mix elements creates added value and strengthens the sustainable competitive advantage of MSMEs in local markets.